Airway Clearance for the Preterm Newborn. Issue 6 (November 2018) - Harbin, Brandi R.; Adams, Ellise D.; O'Neal, Pamela V.
Abstract: Purpose: The purpose of this study was to explore airway clearance practices for the preterm newborn in the neonatal intensive care unit (NICU). Study Design and Methods: This descriptive, retrospective medical record review analyzed airway clearance practices in a level III regional NICU from 2016 to 2017 in preterm newborns ranging from 32 weeks to 36 weeks and 6 days. There were 87 preterm newborns and 384 suctioning events reviewed during the entire length of stay. Practices reviewed include device used, frequency, color, consistency, and tolerance of airway clearance. Method of nursing documentation for these practices was also reviewed. Results: Babies born via cesarean required more suctioning (65.5%). Males (60.9%) required more airway clearance events than females (39.1%). After suction events, nurses reported no distress (74%), equal bilateral breath sounds (30%), desaturation (6%), and collectively color change, apnea, or bradycardia (<1%). The most common discharge diagnosis was respiratory distress syndrome (90%). Preterm newborns were suctioned with the blue bulb syringe (15.6%), oral/nasal-pharyngeal suction device (42.7%), and endotracheal suction devices (41.7%). Clinical Implications: Electronic medical records promote less detailed, narrative documentation and more point and click documentation. If electronic medical record systems are not designed to gather airway clearance indications, specifics about the procedure and the preterm newborn response to the procedure, evidence-based practice cannot be measured. More studies are needed to evaluate suction practices applied in the NICU setting. Abstract : The need for evidence-based clinical guidelines on a national level is crucial to develop protocols, integrate them into clinical practice, and allow for detailed documentation for airway clearance in preterm newborns. Without a well-defined, standardized method of airway clearance, clinical practices may vary. In this study, preterm newborn airway clearance varied significantly among caregivers. This discrepancy can result in negative health outcomes for preterm babies.